Evaluasi Usability dan Perbaikan Antarmuka Pengguna Website Badan Pelayanan Pajak Daerah Kabupaten Sidoarjo - Rafidah Arafahni Miladi; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Local Tax Service Agency of Kabupaten Sidoarjo (BPPD Kab. Sidoarjo) in implementing e-government utilizes a website to assist local tax services and disseminate information about local taxes online for the community and taxpayers. The BPPD Kab. Sidoarjo website itself has several usability-related problems, such as navigation redundancy, placement of important information that is not highlighted, and navigation menus that confuse users. Based on these problems, it is necessary to evaluate usability and improve the user interface to use the website. The research approach uses the Human-centered Design (HCD) method used to design user interface improvements and the heuristic evaluation method to find heuristic problems based on 10 heuristic principles. The problems found in the initial design were then improved based on the evaluator's suggestions and HHS guidelines. The initial design found 46 heuristic problems and the solution design found 23 problems. From the comparison of the evaluation results, it can be said that the solution design is able to reduce usability problems and there is an improvement in usability value on the user interface of the BPPD Kab. Sidoarjo website.